Réponses

2013-01-30T12:26:35+01:00

A= x(2x-7)

B= (x-4)(x-2)

C= 6(2x-1)

D= (x-1)(x+2)

E= -x^2(3x-5)

Meilleure réponse !
2013-01-30T12:28:43+01:00

A = 2x² - 7x = 2x*x - 7x

On factorise par x

A = x * (2x - 7)

 

B = (x-4)² + 2(x-4)

B = (x-4)*(x-4) + 2(x-4)

On factorise par x-4

B = (x-4) ((x-4) + 2)

B = (x-4) (x-2)

 

C = 12x - 6

C = 6*2*x - 1*6

On factorise par 6

C = 6 (2x - 1)

 

D = (1-x)(x+6) - (1-x)(2x+8)

On factorise par (1-x)

D = (1-x) [(x+6) -(2x+8)]

D = (1-x) [x+6 -2x-8]

D = (1-x) [-x-2]

 

E=5x²-3x^3

E = 5 * - 3x*

On factorise par

E = x² (5-3x)